2013
DOI: 10.1108/00070701311289894
|View full text |Cite
|
Sign up to set email alerts
|

CSR failures in food supply chains – an agency perspective

Abstract: Purpose -Companies implement corporate social responsibility (CSR) practices along their supply chains to fulfil stakeholder requirements. In doing so, failures in which CSR aspects are violated also emerge, caused by single supply chain members. In these situations, quite often the other supply chain members also appear responsible although they mostly do not have complete control over suppliers and sub-suppliers due to information gaps. Therefore, the malpractice of one single company can harm the reputation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 32 publications
(49 reference statements)
2
38
0
2
Order By: Relevance
“…(2012) on the use of agency theory in supply chain management and the screening of additional representative studies that take the unit of analysis beyond the dyad and/or specifically addressed sustainability, we found that scholars have not delved deeply into understanding the specific role of the first‐tier supplier in disseminating sustainability standards. For example, Wiese and Toporowski (2013) argue that the complexity of food supply chains implies that lead firms need to rely extensively on their agents (i.e., the direct suppliers) for controlling sub‐suppliers. However, this study is silent on the conditions under which the first‐tier supplier actually accepts this responsibility and begins to manage sustainability considerations autonomously in their upstream processes.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…(2012) on the use of agency theory in supply chain management and the screening of additional representative studies that take the unit of analysis beyond the dyad and/or specifically addressed sustainability, we found that scholars have not delved deeply into understanding the specific role of the first‐tier supplier in disseminating sustainability standards. For example, Wiese and Toporowski (2013) argue that the complexity of food supply chains implies that lead firms need to rely extensively on their agents (i.e., the direct suppliers) for controlling sub‐suppliers. However, this study is silent on the conditions under which the first‐tier supplier actually accepts this responsibility and begins to manage sustainability considerations autonomously in their upstream processes.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…There is a consensus in the literature (de Man & Burns, ; Wiese & Toporowski, ) that both consumers and NGOs regard retailers as responsible for all activities in their supply chain. Thus, sustainability in retailing is not exclusively related to the own activities of the retail company but also dependent on the behavior of their suppliers (Mefford, ; Schramm‐Klein, Morschett, & Swoboda, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It assumes that different actors (NGOs, media) exert sufficient pressure on western companies to force them to develop conduct codes or ethical guidelines that stipulate the conditions under which products and services should be produced in developing countries. While some authors (Wiese and Toporowski, ) consider codes of conduct as useful tools to reduce information asymmetry and increase transparency in the supply chains, others cast doubt on their efficiency. Lim and Phillips () and Lund‐Thomsen and Lindgreen () specify that pressure exerted on suppliers in developing countries has led to fraudulent practices in CSR initiatives in order to avoid the costs associated with compliance.…”
Section: Literature Reviewmentioning
confidence: 99%